Methodical guidelines for seminar classes and independent work on "History of money" - Shyshkina, Y. K. (National Technical University "Kharkiv Polytechnic Institute", 2024)
At the beginning of the 21st century, one of the most pressing problems is the search for new opportunities for further civilizational development. As history shows, it was monetary systems that played one of the most important roles in the economic development of the past. The discipline “History of Money” covers the development of money from ancient times to the present. During its study, students will get acquainted with the most well-known currency systems of the world and will be able to critically assess their role in the socio-economic development of the world. The means to achieve this will be an essay on a proposed or self-selected topic in the form of an abstract. The purpose of this manual is to give the basic knowledge about the history of Ukrainian and foreign currencies, to form a wider worldview and to develop intellectual, moral and aesthetic qualities worthy of a highly educated specialist. The discipline is a synthesis of two approaches. The first one is aimed to study money as historical sources. The second one - to study both formation, ways of transformation of Ukrainian and foreign currencies in the context of socio-economic processes at different stages of development of the Ukrainian and other statehoods.
Методичні вказівки для семінарських занять і самостійної роботи з "Історії грошей"
Keywords: methodical guidelines; origin and types of money; numismatics; bonistics; barter; fist forms of money; ancient coins; first paper money; money circulation in the middle ages; monetary systems in the modern period; forms of money nowadays